A retrospective molecular study of select intestinal protozoa in healthy pet cats from Italy. Issue 2 (February 2015) - Mancianti, Francesca; Nardoni, Simona; Mugnaini, Linda; Zambernardi, Lucia; Guerrini, Alessandro; Gazzola, Valentina; Papini, Roberto Amerigo
The feline gut can harbour a number of protozoan parasites. Recent genetic studies have highlighted new epidemiological findings about species of Cryptosporidium, assemblages of Giardia duodenalis and Toxoplasma gondii . Furthermore, epidemiological studies suggest the occurrence of Tritrichomonas foetus in cats is on the increase worldwide. The prevalence of selected intestinal protozoa was determined by PCR using DNA previously extracted from the faeces of 146 privately owned healthy cats from Italy. Molecular genotyping on T gondii, G duodenalis and Cryptosporidium DNA was achieved. PCR assays were positive in 32 (22.9%) samples. Three animals (2.0%) were positive for T foetus and Cryptosporidium DNA, 15 specimens (10.3%) were positive for T gondii and 11 (7.5%) for G duodenalis . Co-infections were never observed. Results of the typing analysis allowed the identification of Cryptosporidium felis in all cases. The specimens positive for T gondii hinted at clonal genotype I (n = 7), genotype II (n = 1) and genotype III (n = 7). The G duodenalis isolates were referable to assemblages F (n = 9) and C (n = 2). In conclusion, the results obtained in this study add to the literature regarding the epidemiology of these parasites by confirming their presence in the faeces of healthy pet cats.